1997
DOI: 10.1210/endo.138.2.4912
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Resistance to Glucocorticoid-Induced Apoptosis in Rat Thymocytes with Normal Steroid Receptor Function in Vitro

Abstract: Previous studies have shown that although the majority of rat thymic lymphocytes are sensitive to glucocorticoid-induced apoptosis in vivo, a small population of mature thymic lymphocytes remains even after high dose steroid administration. Here, we describe experiments that were performed to understand the molecular basis of the resistance of these cells to glucocorticoid-induced apoptosis. Adrenalectomized rats were treated for 72 h with a bolus dose (5 mg/kg body weight) of dexamethasone to produce a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 48 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The percentages of apoptosis in all populations increased in mice treated with a 5.0 mg corticosterone pellet, except CD4 + CD8 + cells, for which the percentage decreased. This almost certainly reflects the fact that this subpopulation was depleted by 24 hours of elevated corticosterone concentrations (Figure 1), and at least some of the remaining CD4 + CD8 + cells were likely glucocorticoid resistant [23]. However, it should also be noted that an increase in apoptosis was only observed in mice treated with a 5 mg pellet, not in mice treated with a 0.5 mg pellet.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of apoptosis in all populations increased in mice treated with a 5.0 mg corticosterone pellet, except CD4 + CD8 + cells, for which the percentage decreased. This almost certainly reflects the fact that this subpopulation was depleted by 24 hours of elevated corticosterone concentrations (Figure 1), and at least some of the remaining CD4 + CD8 + cells were likely glucocorticoid resistant [23]. However, it should also be noted that an increase in apoptosis was only observed in mice treated with a 5 mg pellet, not in mice treated with a 0.5 mg pellet.…”
Section: Resultsmentioning
confidence: 99%
“…At present we have no explanation for this discrepancy. It has been shown that resistance to glucocorticoid in vivo is not due to an alteration on the glucocorticoid receptor or to expression of Bcl‐2, but rather to some exogenous thymic factor and/or cell–cell contact that probably alters glucocorticoid receptor/signalling [30]. Further studies are needed to define all the possible factors, exogenous and endogenous, which in different circumstances and environments may cause the variability of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…These processes, which may show spatio‐temporal overlapping, normally occur according to strictly regulated inherent programs whose execution depends on signals from neighboring cells as well as the external environment. Glucocorticoids (GC) have long been known to influence cell proliferation and fate; the majority of information relating to the underlying mechanisms of action derives from work on immune cells (1, 2). GC are increasingly being recognized as key players in the development and maintenance of brain structures, particularly the hippocampus.…”
mentioning
confidence: 99%